Antimicrobial efficacy of alternative compounds for use in oral care toward biofilms from caries‐associated bacteria in vitro. Issue 4 (26th July 2018) - Cieplik, Fabian; Kara, Esra; Muehler, Denise; Enax, Joachim; Hiller, Karl‐Anton; Maisch, Tim; Buchalla, Wolfgang
Abstract: For caries‐active patients, antimicrobial measures may be useful in addition to mechanical biofilm removal. The aim of this study was to investigate the antimicrobial efficacy of alternative compounds for use in oral care from two main categories (i.e., preservatives and natural compounds) toward biofilms from caries‐associated bacteria as compared to oral care gold‐standards chlorhexidine digluconate (CHX), cetylpyridinium chloride (CPC), and zinc. Compounds were screened in initial Streptococcus mutans biofilms. Then, the most effective compounds were further investigated in mature S. mutans and polymicrobial biofilms comprising Actinomyces naeslundii, Actinomyces odontolyticus, and S. mutans . Here, distinct treatment periods and concentrations were evaluated. Biofilms were visualized by scanning electron microscopy and bacterial membrane damage was evaluated by means of flow cytometry and staining with SYBR Green and propidium iodide. Citrus extract was the only compound exhibiting similar antimicrobial efficacy in initial S. mutans biofilms (>5 log10 ) as compared to CHX and CPC, but its effect was clearly inferior in mature S. mutans and polymicrobial biofilms. Flow cytometric data suggested that the mechanism of antimicrobial action of citrus extract may be based on damage of bacterial membranes similar to CHX and CPC. From all alternative compounds investigated in this study, citrus extract exhibited the highest antimicrobial efficacy toward in vitro biofilms from caries‐associated bacteria, but still was less effective than oral care gold‐standard antiseptics CHX and CPC. Nevertheless, citrus extract may be a valuable antimicrobial compound for use in oral care for caries‐active patients. Abstract : For caries‐active patients, antimicrobial measures may be useful in addition to mechanical biofilm removal. In this study, several alternative compounds for use in oral care were evaluated for their antimicrobial efficacy toward in vitro biofilms from caries‐associated bacteria and compared to gold‐standards chlorhexidine and cetylpyridinium chloride. Furthermore, biofilms were visualized by scanning electron microscopy and bacterial membrane damage was evaluated by means of flow cytometry in order to provide first mechanistic insights.